Organizing the internal manufacturing complexity elements in adaptation of current manufacturing environment: a fuzzy approach / Mohd Noor Hanif M. R. … [et al.] - M. R., Mohd Noor Hanif; W. M., Wan Hasrulnizzam; A. H., Musfirah; R., Muhammad Ashlyzan; K, Seri Rahayu (Universiti Teknologi MARA, 2022)
Manufacturing industry has been developed outrageously during the past decade. The scenario also applies on Malaysian industry where 22.3% of the economy is generated from the manufacturing industry. Numerous latest concepts and technologies have been implemented by manufacturing firms to increase their productivity, product variety and efficiency. However, these changes also provide certain challenges by increasing manufacturing complexity and decreasing sustainability. Generally, manufacturing complexity is classified into internal and external complexity. This research intends to arrange the elements of internal manufacturing complexity (IMC) according to the priority through the period of enhancing sustainability. IMC elements were clustered into organizational, operational and productivity complexity. Fuzzy analytic hierarchical process was implemented in this research as multi criteria decision making method in IMC management. The results found that IMC priority sequence started with productivity, followed by organizational and operational complexity. Productivity complexity with dominant weightage of 0.5302 was emphasized by three elements which are quality inspection process, cost reduction and time reduction respective to the sequence. Meanwhile, organizational complexity slightly led operational complexity by a difference of 0.059. The results show that the Malaysian manufacturing industry is very keen on the product quality and conforms to the requirements. This research could aid firms and researchers to focus on more important elements in decision making for bigger impact on overall performance